Shelf ready packaging in private label brands - Andrade, Margarida Domingues e (2017)
The Portuguese food retail is in constant transformation: The only surviving mode is though adaptation, innovation, or both at the same time. Unfortunately for some and fortunately for others, the Portuguese market is increasingly competitive, volatile and filled with demanding consumers reactive to small price increases and quality reductions. If a ten-year retrospective was pursued, retailers would appear much more sceptical to the ongoing technological advances than what they are today, being now able to respond effectively to any obstacles they encounter. On the other hand, while there are internal processes common to all of them, proper conduct will make all the difference on the final annual profits. The following case-study will characterize a fundamental operational process capable of saving a great percentage of labour cost per year while improving in-store availability and organizational layout of products. The procedure consists in the implementation of shelf ready packaging displays on almost every type of article in a store, whose company of choice is SONAE and the targeted products are private labelled ones. This movement is gaining adherence not only by the national players but also by international retailers whose intentions are driven by the innumerable operational advantages, commercial revenues and efficiency of production. The case-study will start with a short and concise introduction of both International and Portuguese retailing industry as well as the trends that are triggering the success of current private label brands. As to finalize, there will be expressed senses of evolutional perspectives, challenges and limitations. The case will only consider SONAEmc and its seven distinct food categories, [such as the Salty unit (01), the Sweet unit (02), Hard and Soft drinks (03), Hygiene & Beauty (05), Home cleaning (06), Frozen products (07) and Milk derivatives (08)].